MEMPAPUAKAN INDONESIA: MEMBANGUN PAPUA MELALUI PENETRASI SUMBER DAYA MANUSIA PAPUA DI TINGKAT NASIONAL - Immanuel Franthos Papare; Sudibyo Sudibyo; Pujo Widodo (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2021)
This paper discusses the participation of Papuan in developing Indonesia. This is important because it involves the existence of Papuans in Indonesia. Lack of the sense of belonging, low participation in development and perceptions of Papuans as objects of development are some of the factors of  the spirit of Papuan disintegration. Therefore, efforts are needed to increase Papuan participation in national development through penetration of Papuan, Public Diplomacy in order to foster a sense of belonging and strengthening the spirit of nationalism. The penetration of  Papuan in the structure of the central government, especially in the Ministries and State Institutions, is a more effective approach in shaping the paradigm of Papuans as the owners of the Republic of Indonesia compared to the development of Papuan in the Land of Papua; in addition, psychologically this will encourage recognition the environment will be the existence of Papuans as fellow owners of this country.